Comparison of micro-radiofrequency therapy and tolterodine for the treatment of newly diagnosed overactive bladder: A retrospective cohort study - Tang, Min; Liu, Jin; Zhao, Chesong; Wang, Chengming; Zhang, Qian; Du, Mulong; Meng, Xiaoxin; Li, Pu (Frontiers in Neuroscience, 2023)
Purpose: To retrospectively compare the efficacy and safety of a micro radiofrequency (RF) therapy through urethra versus oral tolterodine tartrate in the treatment of newly diagnosed overactive bladder (OAB). Materials and Methods: 46 newly diagnosed moderate to severe OAB patients were included in this study. 23 among them underwent micro-RF treatment procedure, and the other 23 patients took tolterodine. Bladder diaries were recorded 3 days before treatment and during follow-up period on 1, 3 and 7 weeks after micro-RF therapy or oral tolterodine. Micturition parameters including daily voiding times, daily urge urinary incontinence (UI) episodes, daily urgency episodes, mean volume per micturition, post-void residual volume (PVR), maximum urine flow rate (Qmax), overactive bladder symptom score (OABSS) and quality of life (QoL) score were respectively analyzed. Results: All 46 patients fulfilled either micro-RF or oral tolterodine treatment, as well as the complete follow-up. The incidence of adverse events in the micro-RF group was 8.7% (2/23), and that in the tolterodine group was 43.5% (10/23). Two adverse events happened in micro-RF group were injury to the urethra during catheterization in a man, and urinary tract infection in a woman, both of which were relieved or disappeared after day three. The adverse effect in tolterodine group were mainly dry mouth (4/23), dysuria (5/23), and constipation (8/23), but none of them withdrew from the drug therapy. Compared to pre-therapy, all parameters of both groups including daily voiding times, daily urgency episodes, mean volume per micturition, OABSS and QoL score demonstrated significant improvements during follow-up in 7 weeks after therapy, except for daily UI episodes in tolterodine group. while the above parameters showed bigger improvements in micro RF group than tolterodine group. Besides, the general treatment efficacy of micro-RF was 73.9% (17/23), significantly better than tolterodine (10/23, 43.5%), the difference was 30.4% [95%CI:3.4% to 57.5%], P=0.036. Conclusions: Micro-RF therapy is safe and more effective than oral tolterodine for newly diagnosed moderate to severe OAB. More strong evidences would be provided through a well-designed, prospective, randomized controlled trial.